Does Unilateral High‐Load Resistance Training Influence Strength Change in the Contralateral Arm Also Undergoing High‐Load Training? - Song, Jun Seob; Yamada, Yujiro; Kataoka, Ryo; Hammert, William B.; Kang, Anna; Spitz, Robert W.; Wong, Vickie; Seffrin, Aldo; Kassiano, Witalo; Loenneke, Jeremy P. (Scandinavian journal of medicine & science in sports, 2024)
ABSTRACT Training one limb with a high‐load has been shown to augment strength changes in the opposite limb training with a low‐load (via cross‐education of strength), indicating that within‐subject models can be problematic when investigating strength changes. This study examined if the cross‐education of strength from unilateral high‐load training could augment the strength changes in the opposite arm undergoing the same unilateral high‐load training. 160 participants were randomized to one of four groups: (1) training on the dominant arm followed by the non‐dominant arm (D + ND), (2) training on the dominant arm only (D‐Only), (3) training on the non‐dominant arm only (ND‐Only), and (4) a non‐exercise control. All exercise groups performed 18 sessions of unilateral high‐load elbow flexion exercise over 6 weeks. Participants were compared for changes in 1RM strength and muscle thickness. Changes in strength of the non‐dominant arm were greater in D + ND (2.7 kg) and ND‐Only (2.6 kg) compared to D‐Only (1.5 kg) and control (−0.2 kg), while the changes were greater in D‐Only compared to control. The same finding was observed in the dominant arm. Only the arms being directly trained observed increases in muscle thickness. Unilateral high‐load resistance training increased strength in the opposite untrained arm, without changes in muscle thickness. This cross‐education of strength did not augment the strength changes in the contralateral arm undergoing the same unilateral high‐load training. However, it does not necessarily indicate that within‐subject models are methodologically sound to investigate strength change if both limbs are trained with a high‐load.